Equivalência semântica da versão em português do instrumento Early Childhood Oral Health Impact Scale Semantic equivalence of the Brazilian version of the Early Childhood Oral Health Impact Scale - Flávia Cariús Tesch; Branca Heloísa de Oliveira; Anna Leão (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
O instrumento norte-americano Early Childhood Oral Health Impact Scale (ECOHIS) foi criado para avaliar a qualidade de vida relacionada à saúde bucal de crianças pré-escolares e seus familiares. Para que possa ser utilizado no Brasil é necessário fazer sua adaptação transcultural, sendo a equivalência semântica uma das etapas deste processo. O objetivo deste estudo foi avaliar a equivalência semântica entre o ECOHIS e a sua versão em português. A metodologia incluiu seis etapas: a tradução do ECOHIS, que envolveu duas tradutoras; um pré-teste, em que as duas traduções foram submetidas a vinte responsáveis por crianças de 2 a 5 anos de idade; a unificação das duas versões; duas retraduções feitas independentemente por dois tradutores; a revisão das traduções e retraduções e; a produção de um questionário final. As duas versões traduzidas mostraram-se bastante semelhantes e após a realização de todas as etapas obteve-se uma versão final do ECOHIS. O uso de traduções e retraduções que foram avaliadas por especialistas e incorporaram sugestões da população-alvo, permitiu obter uma versão brasileira do ECOHIS que possui equivalência semântica com o instrumento original. The North American instrument Early Childhood Oral Health Impact Scale (ECOHIS) was created to assess the oral health-related quality of life of preschool children and their families. Its use in Brazil requires prior cultural adaptation, and semantic equivalence is one step in this process. The objective of this study was to evaluate the semantic equivalence between the ECOHIS and its Brazilian version. The methodology included six steps: translation of the ECOHIS into Portuguese, done by two translators; a pre-test, in which the two translations were tested in a group of 20 parents/guardians of children 2-5 years of age; unification of the two versions; two back-translations done independently by two translators; review of the translations and back-translations; and production of a final version of the questionnaire. The two translated versions were very similar, and after completion of all steps a final version of the ECOHIS was obtained. The use of translations and back-translations carefully evaluated by experts and incorporating suggestions from the target population allowed the development of a Brazilian version of the ECOHIS that is semantically equivalent to the original instrument.